Wykonaj działania.Wynik podaj w najprostszej postaci

Wykonaj DziałaniaWynik Podaj W Najprostszej Postaci class=

Odpowiedź :

Odpowiedź:

Zadanie 2

a)

[tex]\frac{1}{3x}+\frac{7}{6x^2}-\frac{5}{2x^3}=\frac{2x^2}{6x^3}+\frac{7x}{6x^3}-\frac{15}{6x^3}=\frac{2x^2+7x-15}{6x^3}[/tex]

b)

[tex]\frac{9x^2-4}{x^2+x}:\frac{3x+2}{5x}=\frac{9x^2-4}{x^2+x}\cdot\frac{5x}{3x+2}=\frac{(9x^2-4)\cdot5x}{(x^2+x)(3x+2)}=\frac{45x^3-20x}{3x^3+2x^2+3x^2+2x}=\frac{45x^3-20x}{3x^3+5x^2+2x}=\frac{45x^2-20}{3x^2+5x+2}[/tex]

Szczegółowe wyjaśnienie: